Child sexual exploitation : why theory matters - Pearce, Jenny J. (Bristol, UK ; Chicago, IL, USA : Policy Press, 2019)
The issue of Child Sexual Exploitation (CSE) is firmly in the public spotlight internationally and in the UK, but just how well is it understood? To date, many CSE-related services have been developed in reaction to high profile cases rather than being designed more strategically. This much-needed book breaks new ground by considering how psychosocial, feminist and geo-environmental theories, amongst others, can improve practice understanding and interventions. Edited by one of the leading scholars in the field, this is an essential text for students and those planning strategic interventions and practice activities in social, youth and therapeutic work with young people, as it supports understanding of how CSE arises and how to challenge the nature of the abuse.
Forward / Julia Davidson -- Bringing theory home : thinking about child sexual exploitation / Jenny Pearce -- Moving beyond discourses of agency, gain and blame : reconceptualising young people's experiences of sexual exploitation / Helen Beckett -- Child sexual exploitation, discourse analysis and why we still need to talk about prostitution / Jo Phoenix -- Contextual safeguarding : theorising the contexts of child protection and peer abuse / Carlene Firmin -- "Losing track of morality" : understanding online forces and dynamics conducive to child sexual exploitation / Elly Hanson -- Understanding adolescent development in the context of child sexual exploitation / John Coleman -- Some psychodynamic understandings of child sexual exploitation / Nick Luxmoore -- Understanding trauma and its relevance to child sexual exploitation / Kristine Hickle -- Social support, empathy and ecology : a theoretical underpinning for working with young people who have suffered child sexual abuse or exploitation / Pat Dolan and Caroline McGregor -- Using an intersectional lens to examine the child sexual exploitation of black adolescents / Claudia Bernard -- What's gender got to do with it? : sexual exploitation of children as patriarchal violence / Maddy Coy -- Understanding models of disability to improve responses to children with learning disabilities / Emilie Smeaton -- Some concluding thoughts / Jenny Pearce.
Title from publisher's bibliographic system (viewed on 19 Mar 2021).
Keywords: Child sexual abuse -- Great Britain